Análisis de flujo de potencia en el alimentador 1 de la subestación San Cristóbal en el área de concesión Elecgalapagos S.A para determinar pérdidas técnicas en las conexiones actuales. - Changotasig Sisalema, José Luis (2017)
Losses of power and electric energy has always been a problem that most power companies have had. This is why this research project aims to identify the technical losses in different elements and equipment that exists in a Distribution System, which goes from the feeder to the final consumer. To carry out this research, it began with an analysis in the distribution system of the feeder 1 of the San Cristóbal Substation of “Elecgalápagos” Company; this analysis allows knowing the behavior of each of its components and their damages to the system, by determining the current state where the distribution network of fedeer 1 is located. For this analysis, there is a methodology based on the management of measurement equipment is used by the CYMDIST software that, thanks to the features and benefits offered by this computational package, it allows to do power flows that shows the network to its most real approximation. Once the deep study of the feeder 1 it is concluded that, the losses occur mainly due to the load unbalance of the feeder, as well as, the inadequate sizing of the conductors as a product of the growth of the backbone and its network branches. Therefore, this research work proposes alternatives such as: load balance, increase of transformers or the repowering of conductors to reduce losses, and improve voltage levels.